POTENSI DAN TANTANGAN INTEGRASI TEKNOLOGI DALAM PEMBELAJARAN AL-QUR’AN HADITS DI MADRASAH ERA DIGITAL - Ahmad Khori; Muhammad Bisri Syamsuri; Aris Warisman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of digital technology has brought significant changes to the education system, including in the context of learning the Quran and Hadith in Islamic schools (madrasas). Integrating technology into the learning process has become a strategic necessity to improve the quality of education and adapt to the demands of the times. This study aims to comprehensively analyze the potential and challenges of technology integration in learning the Quran and Hadith in Islamic schools in the digital era. This research uses a qualitative approach with a literature review, reviewing various relevant scientific sources, such as journal articles, academic books, and previous research. The results indicate that technology integration has significant potential to improve learning effectiveness. Technology enables expanded access to learning resources, increases interactivity through the use of digital media, and supports flexible, student-centered learning. Furthermore, technology also facilitates learning management and evaluation through a structured digital system. In the context of learning the Quran and Hadith, the use of technology such as digital Quran applications, interactive multimedia, and online learning platforms has been shown to enhance students' understanding of the material in a deeper and more contextual way. However, technology integration also faces various complex challenges. Limited technological infrastructure in some madrasas is a major obstacle to implementing digital-based learning. Furthermore, teachers' varying digital competencies impact the effectiveness of technology use in learning. Another challenge relates to values ​​and ethics, where the use of technology has the potential to open access to content inconsistent with Islamic values. Furthermore, uncontrolled technology use can reduce direct interaction between teachers and students, which plays a crucial role in character formation and the internalization of religious values. Based on these findings, it can be concluded that technology integration in Qur'an and Hadith learning in madrasas holds enormous potential, but requires wise and strategic management. Synergy is needed between strengthening infrastructure, improving teacher competency, and developing digital content based on Islamic values. With the right approach, technology can be an effective tool for improving the quality of Qur'an and Hadith learning without neglecting the essence of Islamic education.